EXPLORING THE IMPACT OF ESG DISCLOSURE, DIVIDEND PAYOUT RATIO, AND INSTITUTIONAL OWNERSHIP ON FIRM VALUE: A MODERATED ANALYSIS OF FIRM SIZE - Dihardjo, Jason Ferdianto; Hersugondo, Hersugondo (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2023)
This study explores the effect of environmental, social, and governance (ESG) disclosure, dividend payout ratio (DPR), and institutional ownership on firm value in Indonesia during the period of 2010 "“ 2021 with firm size as a moderating variable. This study examined annual data from a total sample of 58 companies listed on Indonesia Stock Exchange. The panel data was analyzed using a moderated regression analysis. The results demonstrate a negative and significant effect of the ESG disclosure on the firm value. This suggests that the ESG disclosure may increase company costs, resulting in a decrease in the firm value, while the DPR and institutional ownershop have a positive and significant effect as explained by the signalling theory. In addition, the moderating role of firm size on the effect of both the ESG disclosure and institutional ownership on the firm value have a positive and significant effect. These findings imply that big companies can invest in long-term ESG projects beneficial for them, while the institutional ownership on the big companies can reduce information asymmetry. However, the moderating role of firm size on the effect of DPR on firm value does not have a significant effect.JEL: G30, G32, Q01.